Effects of fasting abbreviation through carbohydrate (cho) oral solution in hospital procedures (Research, Society and Development, 2021)
The work aims to prove that there are positive effects in the abbreviation of fasting, using the solution enriched with carbohydrate (CHO) in patients who have undergone hospital interventions. The main objective was to show whether there was an improvement in the patient's clinical condition and to explore the information already existing in the literature. A narrative review was made based on a selection of the main articles on the topic in recent years, in English and Portuguese. An analytical research was also carried out in order to seek answers to the study's problems based on the data found in Scielo, Cochrane, PubMe and the ACERTO protocol for the construction of this work. The research result was quite satisfactory, showing that the abbreviation for fasting is possible because of the action of a multidisciplinary team and the important action of the nutritionist when indicating the abbreviation of fasting to patients. This reduction in fasting brought benefits, such as, well-being, rapid recovery and reduced hospitalization time for hospitalized patients.